Dural arteriovenous fistula of the craniocervical junction manifesting as cerebellar haemorrhage - Inamasu, Joji (Neuroradiol J, 2016)
We report a rare case of dural arteriovenous fistula at the craniocervical junction manifesting as cerebellar haemorrhage, which posed a diagnostic challenge for physicians. A 77-year-old woman with no history of arterial hypertension presented to our Emergency Department with dizziness, and imaging studies revealed a small cerebellar haemorrhage. She was diagnosed with hypertensive intracerebral haemorrhage and conservatively treated. Four months later, she developed subarachnoid haemorrhage, and imaging studies revealed dural arteriovenous fistula at the left C1 dural sleeve. Disruption of a distended cerebellar vein due to venous hypertension by dural arteriovenous fistula was considered to be responsible for intracerebral haemorrhage and subarachnoid haemorrhage. Dural arteriovenous fistula was cured following surgical ligation of a feeding artery and a draining vein. The present case was educational in that effort to identify the cause of bleeding using vascular imaging studies may be important in patients with seemingly typical hypertensive intracerebral haemorrhage, particularly in those without a past history of arterial hypertension.